211k views
0 votes
2x+11=-3(2x-1) solve for x​

2 Answers

5 votes

Answer:

x = - 1

Explanation:

2x+11= -3(2x-1) | distribute

2x+11= -6x+3 | add 6x to both sides

8x+11= 3 | subtract 11

8x = - 8| divide by 8

x = -1

User Kenedy Nopriansyah
by
6.2k points
5 votes

Answer:

x=-1

Explanation:

start by distributing the negative 3 to 2x and negative one. after the equation should look like this:

2x+11=-6x + 3

the next step is to combine the X's

8x+11=3

next step:

8x=-8

next step: divide

8/-8 =-1 so x=-1

User Luka Milani
by
6.1k points